A Case Study of Risk-Based Inspection Implementation in Diesel Fuel Distribution Pipelines - Patria, Mochamad Febrian Adhi; Umam, Mukhamad Faeshol; Krisdiyanto (JMPM (Jurnal Material dan Proses Manufaktur), 2024)
Distribution pipes play an important role in the oil and gas industry, allowing fluids such as crude oil, natural gas, and processed products to move. X Company, an oil and gas company, uses these pipelines to transport diesel fuel from the refinery unit to storage tanks. Proper inspection and maintenance of this pipeline is critical to avoiding issues such as corrosion, cracking, and material failure, which can jeopardize safety, finances, the environment, social stability, legal compliance, and business continuity. This study evaluates a risk-based inspection methodology for ten thickness measurement locations on diesel fuel distribution pipelines using the API 581 standard. The procedure includes a literature review, data collection, assessment of remaining life, calculation of the probability and consequence of failure, risk profiling, and the development of an inspection plan. The results indicate that the pipelines have an average remaining life of 13.14 years. Nine thickness measurement locations were classified as 1C and one as 2C, placing them in the medium-risk category. Every three years, a re-inspection plan is proposed that includes both a 100% visual inspection and targeted non-destructive testing using ultrasonic thickness readings. This study demonstrates how risk-based inspection concepts can be used in practice to improve pipeline integrity inspection procedures. The findings include practical recommendations for increasing safety and operational reliability while reducing inspection costs and risks associated with diesel fuel distribution pipelines.